Developing professional-level language proficiency - Leaver, Betty Lou; Shekhtman, Boris (Cambridge University Press, 2002)
This book examines approaches to teaching students making the transition from 'advanced' or 'superior' proficiency in a foreign language to 'near-native' ability, a level which has been much neglected in the professional literature. This book aims to assist those developing language programmes at this level by filling this serious gap.